Deep-sea benthic megafauna hotspot shows indication of resilience to impact from massive turbidity flow - Bigham, Katharine T.; Rowden, Ashley A.; Bowden, David A.; Leduc, Daniel; Pallentin, Arne; Chin, Caroline; Mountjoy, Joshu J.; Nodder, Scott D.; Orpin, Alan R. (Frontiers in Marine Science, 2023)
Sediment density flows are large scale disturbances that can have dramatic impacts on seafloor animal communities in the deep sea. Seafloor imagery collected in Kaikōura Canyon (New Zealand), before and after a sediment density flow event that included debris and turbidity flows triggered by a 2016 Mw 7.8 Kaikōura Earthquake, shows the recovery trajectory of the animal community in the canyon head in the weeks, months, and years following the disturbance. The canyon community appears resilient to this event, with models estimating full recovery within a minimum of 4.5–5.1 years and as long as 12 years. The implications of the resilience of this deep-sea community are discussed in the context of the local marine protected area, the surrounding fishery, and global seabed mining.